Synthesized akhtenskites remove ammonium and manganese from aqueous solution: removal mechanism and the effect of structural cations. Issue 53 (15th October 2021) - Zhang, Ruifeng; Yang, Shilian; Dong, Chuan; Qiao, Yu; Zhang, Jianmin; Guo, Yingming
Abstract : Akhtenskites merely remove NH4 + by adsorption, but remove Mn 2+ by adsorption and catalytic oxidation simultaneously. The removal efficiency and crystal structure are obviously affected by the structure cations. Abstract : Ammonium and manganese removal by tunnel-structured manganese oxide is still enigmatic. Herein, tunnel-structured akhtenskites with different structural cations (Na–MnO x, Mg–MnO x Ca–MnO x, Fe–MnO x ) were synthesized by the KMnO4 and Mn 2+ reaction in the presence of different metal cations, and were used to remove ammonium and manganese from aqueous solution. The results of the batch adsorption experiments indicated that akhtenskites effectively removed NH4 + and Mn 2+, and the removal process fitted the pseudo-second-order model. By measuring the concentration of nitrate and nitrite, discriminating the adsorbed and oxidized Mn 2+, and testing the zeta potential of the oxides, it can be concluded that NH4 + was merely removed by electrostatic adsorption via Mn–O − ; Mn 2+ could also be adsorbed by ion exchange with Mn–OH, and the adsorbed Mn 2+ could be partly oxidized. The structural properties of the akhtenskites were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) specific area, and X-ray photoelectron spectroscopy (XPS). The experimental results showed that ions with higher valence can result in a higher percentage of Mn(iii ) in akhtenskite. Mg 2+ can result in a lower proportion of lattice oxygen in the oxide, and Fe 3+ can increase the pH of the point of zero charge. Both of them were unfavored for the oxidation of Mn 2+ . Moreover, it was found that Ca–MnO x had optimal removal performance in the catalytic oxidation of Mn 2+ owing to appropriate percentages of Olatt and Mn(iii ) and lower zeta potential. This study provides new insights into the synthesis and application of manganese oxides.